PERILAKU PENGGUNAAN KONDOM PADA LAKI-LAKI OPERATOR KARAOKE DALAM PENCEGAHAN PENULARAN HIV DAN AIDS DI KOTA SEMARANG - Oktaviani Cahyaningsih (Dian Nuswantoro Semarang, 2016)
Cases of HIV / AIDS continues to increase very fast, HIV virus can lead to decreased levels (CD-4) in patients so it is easy to get opportunistic infection. According to data from the Ministry of Health from 1 April 1987 to 30 September 2014 found 150.296 cases of HIV and 55.700 AIDS cases. Operator Karaoke is one of the professions that at risk because they have partners in the localization and also outside, such as wives or girlfriends.Obligations of 100% condom useÂ has been proclaimed long time ago as the National Strategy to suppress the spread of HIV / AIDS, yet the reality is more preferred to reach female sex workers, transvestites, MSM and IDU so that it can be concluded not to specifically reach Operator Karaoke, which is one of the professions-risk also in the spread of HIV / AIDS.This study aimed to analyze the factors that influence condom use in men at high risk (operator ) in preventing the transmission of HIV / AIDS in Argorejo Resocialization. This was explanatory research, with cross sectional approach and survey to collect the data. The results shows there was relationship between knowledge, attitude and practice of condom use. Factors unrelated to the practice were the age, education, religiousity and the status of marriage.Keywords : Karaoke operator, condom use